Collaborative Facilitation in Older Couples: Successful Joint Remembering Across Memory Tasks - Barnier, Amanda J.; Harris, Celia B.; Morris, Thomas; Savage, Greg (Frontiers in Psychology, 2018)
Although we know a great deal about the effects of age on memory, we know less about how couples remember together and how day-to-day joint remembering might support memory performance. The possibility of memory support when couples remember together is in striking contrast with the standard finding from the collaborative recall literature that when younger pairs of strangers remember together they impair each other’s recall. In the current study, we examined the individual and joint remembering of 78 individuals who made up 39 elderlyolder, long-married couples. We studied their performance on three memory tasks, varying in personal relevance: recalling a word list, listing all the countries in Europe, and remembering the names of their mutual friends. Couples gained clear collaborative benefits when they remembered together compared to when alone, especially European countries and mutual friends. Importantly, collaborative success was extremely stable over time, with good collaborators still successful two years later, suggesting that successful collaboration may be a stable couple-level difference. However, not all couples benefitted equally. Collaborative success related in part to particular conversational strategies that some couples, often those with discrepant individual abilities, used when collaborating. These findings highlight the value of analysing individuals within their broader “memory systems” and the power of extending collaborative recall methods to more established intimate groups recalling a broader range of memory materials over longer time scales.